Strategic tools and business modeling in an information technology firm - Keller, Felipe Hatzenberger; Daronco, Everaldo Luis; Cortimiglia, Marcelo (Brazilian Journal of Operations & Production Management, 2017)
Many small companies active in the segment of information and communication technology demonstrate difficulties in terms of expanding their business and increasing the product and service portfolio. In this context, this study aims to apply strategic tools and business model in a micro-segment of the software industry inserted into a huge market competition and low entry barriers. A qualitative research was carried out, unfolded in three stages: initial diagnosis, which is developed in the current map of the business model and analysed in the internal and external environments through tools such as PESTEL, Porter's 5 forces and SWOT matrix; critical analysis, when opportunities for improvement were identified based on analysis of the environment and questionnaires applied to current and potential customers and; restructuring and identifying improvements, a stage that includes the redesign of the idealized business model, stipulating coefficients of importance for further start-up study, by applying cross SWOT analysis. Among the main results to new technologies, media release, complementary services and support partnerships are adapted.